Prophylactic and Therapeutic HPV Vaccines: Current Scenario and Perspectives - Mo, Yicheng; Ma, Jiabing; Zhang, Hongtao; Shen, Junjie; Chen, Jun; Hong, Juan; Xu, Yanmin; Qian, Cheng (Frontiers in Cellular and Infection Microbiology, 2022)
Persistent human papillomavirus (HPV) infection is recognized as the main cause of cervical cancer and other malignant cancers. Although early detection and treatment can be achieved by effective HPV screening methods and surgical procedures, the disease load has not been adequately mitigated yet, especially in the underdeveloped areas. Vaccine, being regarded as a more effective solution, is expected to prevent virus infection and the consequent diseases in the phases of both prevention and treatment. Currently, there are three licensed prophylactic vaccines for L1-VLPs, namely bivalent, quadrivalent and nonavalent vaccine. About 90% of HPV infections have been effectively prevented with the implementation of vaccines worldwide. However, no significant therapeutic effect has been observed on the already existed infections and lesions. Therapeutic vaccine designed for oncoprotein E6/E7 activates cellular immunity rather than focuses on neutralizing antibodies, which is considered as an ideal immune method to eliminate infection. In this review, we elaborate on the classification, mechanism, and clinical effects of HPV vaccines for disease prevention and treatment, in order to make improvements to the current situation of HPV vaccines by provoking new ideas.